Effectiveness of exercise therapy on pain relief and jaw mobility in patients with pain-related temporomandibular disorders: a systematic review - Shimada, Akiko; Ogawa, Toru; Sammour, Sara Reda; Narihara, Taichi; Kinomura, Shiori; Koide, Rie; Noma, Noboru; Sasaki, Keiichi (Frontiers in Oral Health, 2023)
Background: Orofacial pain conditions are complex disorders that involve biological, social, and psychological factors. Temporomandibular Disorders (TMDs) are one of the most common orofacial pain conditions, and our previous literature review indicated that exercise therapy has shown promise in reducing TMD-related pain. However, more evidence is needed to firmly establish its effectiveness. Objectives: This systematic review aims to investigate the effectiveness of exercise therapy on pain relief and jaw mobility in patients with pain-related TMDs. Methods: To include randomized controlled trials (RCTs) written in English, a literature search was performed using PubMed, Scopus, Web of Science, Cochrane Library, Ovid, EBM reviews, and Academic Search Complete initially from 4th November 2020 until March 2022. A PICOS for this review was as follows; P: Patients with TMD myalgia or arthralgia, I: Excursion exercise, Stretch exercises, Resistance exercise, or Coordination exercise, C: No treatment or education only. O: Pain intensity and Range of Motion (ROM), S: RCTs. After title screening, a full-text assessment was done to extract data. According to Risk of Bias (RoB) 2.0, risk of bias was assessed in each included paper by 2 reviewers independently. Results: A total of 3388 titles were identified from the electronic database search. After the screening and full-text evaluation, only 5 studies (145 participants) were eligible to be included. Among the exercise modalities, coordination exercise showed a significant effect on pain relief and improvement of joint mobility. Discussion: Due to the heterogeneity and small sample size of the included studies, a meta-analysis was not feasible. However, this systematic review suggested that exercise therapy, especially coordinate exercise, can be effective in managing painful TMD conditions. Further research is needed to establish optimal parameters for this patient population, as well as standardization and consistency in terminology and treatment structure.